Coexistence of Pulmonary Hypertension and Galen Vein Aneurysm in Newborns - Muhammet Bulut; Dilek Küçük Alemdar; Kıvanç Çelikkalkan; Emine Tekin; Özge Eren; Handan Ayhan Akoğlu; Azime Bulut; İlknur Okur Akşan; Seyyit Bahaettin Öncü (Çocuk Dergisi)
Objective: We aimed to consider Galen vein aneurysm(GVA) in cases that may often get a diagnosis later due to the pre-diagnoses of transient tachypnea of newborn and congenital heart disease accompanied by moderate-severe pulmonary hypertension in the postpartum period.Method: The study included cases that were followed and treated with the diagnosis of GVA in our clinic between 2016-2020. Types of delivery, week of delivery, birthweight/height/head circumference, medical treatments, and imagings were recorded from patient files. The risk evaluation was performed according to Bicetre and the scoring was recorded.Results: Of our cases; 80% (n=4) were female, and 80% (n=4) had been delivered via spontaneous vaginally. Their week of delivery was 39.20±.83 (min:38, max:40), birth weight was 3488±415 gr, head circumference was 36.20±1.30 and height was 51.20±1.30 cm. Firstly, all cases had tachypnea, dyspnea, cyanosis, and tachycardia. Of our cases, three were intubated, others (4.5) received non-invasive support only. The patient (infant 3) with a lower Bicetre score did not stabilize and died. One of our cases (infant 4) whose Bicetre score was above 12, was operated electively. In all cases the GVA was accompanied by persistent pulmonary hypertension (PPHT). The cases that had severe PPHT and did not improve despite inotrop treatment died.Conclusion: Galen vein aneurysms should certainly be considered in PPHT cases in the early stage of those that don’t respond to multiple treatment options.